Cadastral Data Model for an Informal Settlement: Case Study of Huruma, Nairobi – Kenya - Malachi Odongo Atieno; David Siriba (African Journal on Land Policy and Geospatial Sciences, 2019)
The complexity of tenure claims in the informal settlements has been difficult to incorporate into the formal systems owing to their dynamic and continuously changing nature. Innovative tools are therefore required to capture these claims. This requires the development of a cadastral data model specifically for informal settlements that would document such claims to make it easier to manage the current situation as well as prepare for future formalization processes such as regularization or relocation. The main aim of this study was develop a typology of informal settlements in Kenya as a basis for developing a cadastral data model. A data model was developed based on the Social Tenure Domain Model (STDM) using open source geo-solution (SOLA).  The model was found to be generally suitable for all the different informal settlement typologies.